Rituximab in Multiple Sclerosis: Are We Ready for Regulatory Approval? - Brancati, Serena; Gozzo, Lucia; Longo, Laura; Vitale, Daniela Cristina; Drago, Filippo (Frontiers in Immunology, 2021)
Despite the availability of a lot of effective disease modifying drugs, multiple sclerosis (in particular the progressive forms) still represents an important unmet medical need, due to issues in terms of effectiveness, duration of response, safety and patient compliance. An increasing body of evidence from randomized clinical trials and real-world data suggest that rituximab is a highly effective alternative in both relapsing and progressive MS, with a low discontinuation rate, related to a good benefit/risk profile and a good compliance. To date the use of rituximab in patients with multiple sclerosis is not in accordance with the authorized product information (off-label use). However, the use of this medicine is widespread in several countries, and in some cases, it is the most commonly used disease modifying drug for MS subtypes. This use could be officially recognized by national regulatory authorities, according to specific procedures, to ensure equal access for patients to a safe and effective option.